Do we really want to know? The journey to implement empirical research recommendations in the ICRC's responses in Myanmar and Lebanon. Issue 2 (23rd November 2022) - Leresche, Enrica; Hossain, Mazeda; Rossi, Rodolfo; Truppa, Claudia; Barth, Cornelia Anne; Mactaggart, Islay; Leaning, Jennifer; Singh, Neha
Abstract : Efforts to reduce the gap between the research evidence base and humanitarian responses have focused on producing quality evidence and ensuring its use in decision‐making. Yet, how evidence translates into field‐level implementation is not well understood in humanitarian contexts. This study analysed how recommendations produced through academic research partnerships were implemented by the International Committee of the Red Cross (ICRC) in Lebanon and Myanmar. The methodology included: social network analysis to represent collective dynamics; document reviews to assess implementation; qualitative interviews to comprehend why actors engaged; and a critical appraisal of these combined results. The application of Extended Normalization Process Theory provided information on 'anticipation of constraints' (access to information, staff turnover, context specificity, and the need to engage as a cohesive group). Future research efforts should concentrate explicitly on identifying and tackling implementation barriers such as power imbalances and ethical dilemmas related to service delivery by humanitarian actors. المستخلص: ركزت الجهود لتقليل الفجوات بين أساس أدلة البحث والاستجابات الإنسانية على إنتاج أدلة ذات جودة وصالحة لاستخدامها في اتخاذ القرار. وعلى الرغم من ذلك فإن كيفية ترجمة الأدلة إلى نطاق التنفيذ على المستوى الميداني ليس مفهوماً بشكل جيد تماماً في السياقات الإنسانية. قامت هذه الدراسة بتحليل كيف أن التوصيات التي أنتجها البحث الأكاديمي قد تم تنفيذها من قِبل اللجنة الدولية للصليب الأحمر (ICRC) في لبنان وميانمار. وبناء على نظرية التنفيذ، فإن المنهجية شملت تحليل الشبكات الاجتماعية لتمثيل ديناميكيات مجتمعة؛ واستعراض الوثائق لتقييم التنفيذ؛ والمقابلات النوعية لفهم سبب تفاعل الجهات الفاعلة؛, وتقدير خاص لكل تلك النتائج المجتمعة. ووفر تطبيق نظرية التنفيذ معلوماتٍ حول "توقع القيود" (الوصول إلى المعلومات، تغير الموظفين، تخصيص السياق والحاجة إلى إشراك مجموعة متماسكة). يجب أن تركز الجهود البحثية المستقبلية تركيزاً واضحاً على تحديد والتعامل مع عوائق التنفيذ من أمثال اختلالات القوى والإشكاليات الأخلاقية المتعلقة بإيصال الخدمة من طرف الجهات الإنسانية الفاعلة. الكلمات المفتاحية: مناطق النزاع، الإنساني، التنفيذ، اللجنة الدولية للصليب الأحمر، البحوث التشغيلية، الشراكة، استيعاب البحوث 摘要: 为了缩小研究证据基础和人道主义行动之间的差距，大量的努力花费在了产出高质量的证据并确保其用于决策上面。然而，在人道主义行动方面，人们并没有很好的理解如何将证据转化成实际行动。这项研究分析了黎巴嫩和缅甸的红十字国际委员会（ICRC）是如何实施来自合作学术研究伙伴给出的建议的。基于实施理论，采用的方法和目的如下，用社交网络分析代表集体动力学；用文件审查评估实施情况；用定性访谈了解行为者参与的原因；以及对这些方法产生的所有的结果的批判性评价。实施理论的应用为 "限制因素的预期 "提供了信息（信息的获取、工作人员的流动、环境的特殊性以及雇佣一个有凝聚力的团体的必要性）。未来的研究工作应明确地集中在确认和解决实施面临的障碍上，比如，权利不平衡和提供援助时面临的道德困境。 关键词：冲突环境；循证；人道主义；实施；红十字国际委员会（ICRC）；行动研究；伙伴关系；研究成果使用